Incineration of tannery waste in a tunnel furnace system = Spalanie odpadów garbarskich w piecu tunelowym - Famielec, Stanisław; Wieczorek-Ciurowa, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The leather industry generates significant amounts of waste for which there is not comprehensive treatment method. Such waste is mainly landfilled, which is an environmental threat. However, solid tannery waste could be incinerated since it contains organic matter. This paper describes research on the incineration of solid tannery waste which was conducted on an experimental installation with a tunnel furnace as the main component. The paper includes brief characteristics of tannery waste and the experimental installation overview. Further on, the experimental conditions as well as measurements and residue analysis results are presented.
Keywords: odpady garbarskie; spalanie odpadów; piec tunelowy; tannery waste; tunnel furnace; waste incineration; waste treatment